Loading of Cells with Fluorescent Probe to Study Intracellular Acid-base Homeostasis in Lactic Acid Bacteria - Pablo Mortera; Federico Zuljan; Christian Magni; Sergio Alarcón (Bio-Protocol, 2015)
Here we describe a protocol which we have used to study the homeostasis intracellular in vivo in lactic acid bacteria (LAB) using a fluorescent probe. This type of probes can be used for determining changes in the pH of cytoplasm with high sensitivity, temporal resolution and technical simplicity as well as accessing the rate of change of intracellular pH in response to a stimulus from kinetic measurements on short time scales (Breeuwer et al., 1996; Molenaar et al., 1991). This protocol has been designed to measure the intracellular pH using the pH-sensitive fluorescent probe 2´,7´-bis-(2-carboxyethyl)-5(and-6)-carboxyfluorescein (BCECF) in LAB, Enterococcus faecalis (E. faecalis), Lactococcus lactis (L. lactis) and Lactobacillus casei (L. casei).